THE ANCIENT ROLE OF COLORS IN TEXTILE ADORNMENT: वस्त्र अलंकरण में रंगों की पुरातन भूमिका - Kumar, Mukund (International Journal of Research -GRANTHAALAYAH, 2014)
Color is the base of textile design (ornamentation). The selection of color materials (kalamedhas) and their application techniques, depending on the text, is based on the artist's personal vision and experience. Colors have a profound effect on a person's feelings. By studying these aspects, pigment is successfully used according to the variety of fabrics. The art of textile dyeing is very ancient. Many such evidences are found in India in which humans had knowledge about textile weaving and textile dyeing. रंग वस्त्र आकल्पन (अलंकरण) का मूलाधार है। वस्त्र्ा के अनुरूप रंग द्रव्य¨ं ;कलमेद्ध का चयन और उनके प्रय¨ग की तकनीक, कलाकार अथवा रंगरेज के निजी दृष्टिक¨ण एवं उनके अनुभव पर आधारित ह¨ती है। रंग¨ं का, व्यक्ति की मन¨भावनाअ¨ं पर गहरा प्रभाव पड़ता है। इन्हीं पहलुअ¨ं का अध्ययन करके वस्त्र्ा¨ं के विविध प्रकार के अनुसार रंगद्रव्य का सफलतापूर्वक प्रय¨ग किया जाता है। वस्त्र्ा रंगाई की कला अतिप्राचीन है। भारतवर्ष में कई ऐसे प्रमाण मिलते हैं जिनमें वस्त्र्ा बुनाई एवं वस्त्र्ा-रंगाई के विषय में ईसा पूर्व एवं उत्तरार्ध में मनुष्य¨ं क¨ ज्ञान था।